Pengawasan Partisipatif pada Pemilu 2024 di Kabupaten Bintan oleh Saka Adhyasta Pemilu - Siti Delvira Zukni; Bismar Arianto; Eki Darmawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The election supervision function is the authority of Bawaslu, thus Bawaslu needs participatory supervision. The participatory supervision carried out by Bawaslu is by involving community groups such as NGOs, and other organizations. Therefore, Bawaslu Bintan formed Saka Adhyasta Pemilu to assist in overseeing the implementation of elections and following up on violations that occur. This study aims to evaluate the quality of participatory supervision carried out by Saka Adhyasta Pemilu in the 2024 elections in Bintan Regency. The research method used is qualitative with data collection through interviews, field notes, and official documents. There are 4 indicators of participatory supervision according to Pasaribu (2011), namely monitoring, inspection, guidance and direction, and correction. The results showed that the indicators of monitoring, inspection, and correction were still not effective, as seen from the lack of violation reports submitted to Bawaslu by Saka Adhyasta Pemilu. However, in the guidance and direction indicator, it has proven effective because Bawaslu has provided education on monitoring and preventing disputed violations in the 2024 elections in Bintan Regency. The factors that make participatory supervision carried out by Saka Adhyasta Pemilu not run well are because of their young age, lack of critical attitude, lack of experience and minimal knowledge of elections.